The Strategy Building Competitive Advantage of Integrated Islamic Elementary School of Ar Raihan Bantul and Integrated Islamic School of Luqman Al-Hakim Yogyakarta - Hifza,; Karyono, Otong; Harlina,; Syakhrani, H. Abdul Wahab; Ainiyah, Qurrotul (International Journal of Psychosocial Rehabilitation, 2025)
The strategy of building competitive excellences in the Integrated Islamic Elementary School (SDIT) is an effort to gain higher achievements while overcoming the problem of cause and effect that envelops the journey of private Islamic educational institutions. The purpose of the study was to analyse and find the choosen strategies and steps in building a competitive advantage. To get the data needed, this study used a qualitative approach, with the type of case study and multi-site design. The results showed that the strategy of building a competitive excellency at SDIT was a strategy focused differentiation based on religious, with steps as follows: a) differential product on curriculum and program Tahfiz Al-Qur'an; b) differentiation of leadership competencies and human resources; c) differentiating service quality through financial innovation, religious culture and quality culture; d) differentiating cohesiveness in work teams and cooperation networks; and e) differential image with academic achievements and hafizh (memorising) the Al-Qur'an.